DNA methylation changes in aging cells and tissues - Issa, Jean-Pierre (Henry Stewart Talks, 2011)
Epigenetics, Phenotypic variation, DNA methylation, Promoter CpG & Non CpG islands, The methylome, DNA methylation changes in aging, Hypermethylation and silencing, Methylation in normal colon vs. age, Microarray analysis of aging human colon, Methylation in aging human prostate, Methylation vs. age in human right atrium, MCAM analysis of aging mouse colon, Pyro analysis of aging mouse colon, Age related methylation along the GI tract, Epigenetic mosaicism, Human carcinogenesis as an epigenetic disease, Changes in tissue function, Tissue function consequences of DNA methylation changes in aging, Epigenetic variation in human colon, Susceptibility to DNA hypermethylation, DNA hypermethylation and retrotransposons, Genome-wide analysis of methylation proneness, Genome architecture and the prediction of hypermethylation, Repeat element distribution and age-related methylation, Polycomb targets and hypermethylated genes in aging